PENERAPAN MODEL SNOWBALL THROWING TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA - Andriana, Ramadhani Fitri, (Menara Ilmu, 2018)
This research is motivated by the lack of understanding of the mathematical concepts ofstudents in the of SMK 1 Batang Peranap, students have not been actively involved in thelearning process, some students have not fully mastered the material that has been taughtby teacher, student mathematical thinking ability is not fully developed. The method usedin this study is Quasi Experiment Design with shapes Subjects Randomized Posstest OnlyControl Group Design. Analysis of the data used in this test using normality test,homogeneity test and t-test. Based on the calculation of the t-test (hypothesis test) showeda significant value Sample class is smaller than α is 0.009 <0.05. Based on these results itis H0 rejected and Ha accepted. Understanding of mathematical concepts using SnowballThrowing learning model is better than the students' understanding of mathematicalconcepts using conventional learning class X SMK 1 Batang Peranap.KEYWORDS: Model Snowball throwing, Concept Training